Manajemen Koperasi Gema Nusa Gerakan Pemuda Ansor Kecamatan Cilongok Kabupaten Banyumas Tahun 2023 - hidayah, tonah; Amanda, Ariesta; Sutikno, Chamid (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of this research is to analyze the management of the Gema Nusa Cooperative in an effort to improve the welfare of its members and support local socio-religious organizations. The research method used is a qualitative approach with a case study design. Data collection was conducted through interviews, observations, and documentation studies. Data analysis includes three data processing flows, namely data reduction, data presentation, and conclusion drawing. Data validation uses data triangulation, which is a data collection technique that combines various existing data and sources. The results show that Gema Nusa Cooperative has implemented management functions quite well, but still has some weaknesses in terms of strategic planning and supervision. Therefore, Gema Nusa Cooperative needs to develop a comprehensive organizational strategic planning, develop an effective and efficient organizational structure, and apply the principles of good cooperative governance that includes a performance monitoring and evaluation system, performance feedback, and responsive and collaborative problem solving. Collectively, with the increase in management capacity, it is expected that Gema Nusa Cooperative can be more optimal in improving the welfare of its members.